Oral prednisone for chronic active liver disease: dose responses and bioavailability studies. Issue 12 (December 1978) - Uribe, M; Schalm, S W; Summerskill, W H; Go, V L
Abstract : Serum concentrations of prednisolone were measured by radioimmunoassay after the administration of prednisone (10, 20, or 30 mg) by mouth to five healthy volunteers, five patients with severe chronic active liver disease (CALD), and five patients with CALD in remission induced by prednisone. Only minor differences were found between the groups and bioavailability was linearly related to the dose of prednisone (r = 0.993). After prednisone (10 mg) was given by mouth and by vein to similar groups of volunteers and 11 additional patients with CALD, bioavailability of oral prednisone approximated 100% of the intravenous dose and no differences were found in the pharmacokinetics of prednisolone. We conclude that prednisone is effectively absorbed and converted to prednisolone in health and CALD and find no pharmacological evidence that either drug would be superior to the other for treating CALD.